PROMISING TOMATO CULTIVARS SUITABLE FOR MECHANIZED HARVESTING AND TRANSPORTATION - V. I. Donskaya; N. K. Katakaev (Овощи России, 2017)
The most part of tomatoes cultivated in Astrakhan oblast are transported in industrial centers of Russian Federation. Introduction of new cultivars suitable for mechanized harvesting and transportation has a considerable significance for tomato production in Nizhniye Povolzhye, and consequently, increases the profitability of vegetable production. At All-Russian Research Institute of Vegetable, Melon and Ground Growing several new-bred tomato cultivars passed the trial test, and thus, were shown to meet all requirements for upto-date agricultural technology.Two tomato cultivars 'Bokserskiy' and 'Klasicheskiy' were bred on the base of experimental data. These cultivars exceeded the standard 'Moriyana' in yield capacity, fruit weight, and had nearly equal biochemical composition. According to results obtained, it was shown that the fruits of cultivars 'Bokserskiy' and 'Klassicheskiy' were suitable for mechanized harvesting and long distance transportation.